Prevalence of and risk factors for diabetic retinopathy in residents with different types of abnormal glucose metabolism with or without hypertension: A suburban community-based cross-sectional study - Ma, Yuhang; Wang, Hao; Jiang, Junyi; Han, Changjing; Lu, Chunhua; Zeng, Siliang; Wang, Yufan; Zheng, Zhi; Peng, Yongde; Ding, Xiaoying (Frontiers in Endocrinology, 2022)
Aims: The present study examined the prevalence and risk factors for diabetic retinopathy (DR) in residents with abnormal glucose metabolism in a community. Methods: 6029 subjects were included and underwent standardized interviews and comprehensive examinations. Residents with diabetes were divided into nondiabetic retinopathy (NDR) and DR groups and non-hypertension and hypertension groups. Unconditional multivariate logistic regression models were used to analyze the risk factors for DR in different groups. Results: The prevalence of DR in diabetes was 9.9%, and the prevalence of retinopathy, which also has the typical signs of DRs, such as retinal microaneurysms, in prediabetes and normal glucose tolerance was 5.2% and 5.3%, respectively. An elevated waist-to-hip ratio (WHR) (female≥0.85, male≥0.9)[OR 1.683, 95% CI (1.016, 2.790)], systolic blood pressure (SBP)≥140 mmHg [OR 1.875, 95% CI (1.158, 3.034)], elevated HbA1c [OR 1.410, 95% CI (1.220, 1.629)], HbA1c ≥6.5% [OR 2.149, 95% CI (1.320, 3.498)], antidiabetic drug use [OR 3.798, 95% CI (2.209, 6.529)], elevated fasting blood glucose [OR 1.176, 95% CI (1.072, 1.289)], elevated postprandial blood glucose [OR 1.090, 95% CI (1.033, 1.150)] and nonspecific ST-T segment changes on electrocardiography [OR 2.555, 95% CI (1.556, 4.196)] were risk factors for DR. Duration of diabetes [OR 1.206, 95% CI (1.028, 1.415)], elevated WHR [OR 3.796, 95% CI (1.144, 12.603)], elevated waist circumference [OR 6.874, 95% CI (1.403, 33.665)], elevated HbA1c [OR 1.435, 95% CI (1.046, 1.970)], HbA1c ≥6.5% [OR 6.850, 95% CI (1.771, 26.501)], and concurrent metabolic syndrome [OR 3.975, 95% CI (1.144, 13.815)] were risk factors for DR in diabetes without hypertension, and elevated HbA1c [OR 1.395, 95% CI (1.183, 1.645)], HbA1c ≥6.5% [OR 1.745, 95% CI (1.027, 2.966)], use of antidiabetic drugs [OR 4.781, 95% CI (2.624, 8.711)], elevated fasting blood glucose [OR 1.146, 95% CI (1.034, 1.270)], elevated postprandial blood glucose [OR 1.083, 95% CI (1.020, 1.151)], and nonspecific ST-T segment changes on electrocardiography [OR 2.616, 95% CI (1.531, 4.469)] were risk factors for DR in diabetes with hypertension. Conclusion: Retinopathy was found in subjects with normal glucose tolerance and prediabetes. There were differences in risk factors for DR in diabetic patients with and without hypertension.